FOOD WASTE DALAM KONSTELASI EMPAT PILAR KEAMANAN PANGAN DI KAWASAN ASIA TENGGARA - aipi, triono; Nizmi, Yusnarida Eka; Triono; Eka Nizmi, Yusnarida (Universitas Islam Negeri Raden Intan Lampung, 2024)
Food waste behavior contributes to food security in Southeast Asia, in the context of ensuring the four pillars of food security. Fulfillment of these four pillars of food security is closely related to the increasing prevalence of food waste in Indonesia. This study employed qualitative methods, collecting data through Focus Group Discussions (FGDs) and literature review. The concept of Food Security served as the primary framework for explaining the relationship between food waste and the four pillars of food security. The study results show that Southeast Asian communities face various challenges in meeting their needs for healthy and sufficient food. The four pillars of food security food availability, economic and physical access, utilization, and stability must be strengthened to address issues such as import dependence, the impacts of climate change, and distribution disparities. Each country faces unique challenges, but all require integrated solutions, such as increasing agricultural yields, improving distribution, and educating about healthy eating habits. Cooperation between countries and various stakeholders is crucial to ensuring food security in the region. ASEAN can facilitate joint initiatives, such as regional food reserves and sustainable agricultural technologies. Governments, the private sector, and communities also need to work together to create an equitable food distribution system. With these steps, Southeast Asia can meet its population's food needs while better addressing global challenges.